Cognitive Bias in Adult Zebrafish (Danio rerio): A Systematic Review - Valentina Gazzano; Asahi Ogi; Francesca Cecchi; Maria Claudia Curadi; Maria Marchese; Angelo Gazzano (Veterinary Sciences)
Objective: In recent years, the use of zebrafish (Danio rerio) as laboratory models has significantly increased. Ensuring their welfare is crucial, with the cognitive bias test emerging as a valuable tool to assess their emotional state. This systematic review examines the application of the cognitive bias test in zebrafish research. Data: The review adhered to PRISMA guidelines. Sources: A systematic search was conducted in scientific databases, including PubMed and Scopus, yielding 30 articles. Additionally, one abstract identified through bibliographic screening of selected papers was included. Study Selection: Six studies were selected for analysis, and their quality was assessed using SYRCLE’s risk-of-bias tool. Results: Three experimental models were employed to conduct the cognitive bias test in zebrafish, focusing on the relationship between their affective state and environmental conditions, cognitive abilities, and life-history strategies but none of the studies adequately reported the techniques employed to reduce bias. Discussion: The cognitive bias test proved effective in assessing the emotional state of zebrafish; however, methodological biases may have influenced the results. Conclusion: The cognitive bias test offers valuable insights into how emotional states affect cognitive abilities, responses to environmental changes (e.g., physical enrichment), and stress responses. Further research addressing methodological limitations is necessary to validate these findings and improve data reproducibility.